The Role of BiP Retrieval by the KDEL Receptor in the Early Secretory Pathway and its Effect on Protein Quality Control and Neurodegeneration - Jin, Hisayo; Komita, Mari; Aoe, Tomohiko (Frontiers in Molecular Neuroscience, 2017)
Protein quality control in the early secretory pathway is a ubiquitous eukaryotic mechanism for adaptation to endoplasmic reticulum (ER) stress. An ER molecular chaperone, immunoglobulin heavy chain-binding protein (BiP), is one of the essential components in this process. BiP interacts with nascent proteins to facilitate their folding. BiP also plays an important role in preventing aggregation of misfolded proteins and regulating the ER stress response when cells suffer various injuries. BiP is a member of the 70-kDa heat shock protein (HSP70) family of molecular chaperones that resides in the ER. Interaction between BiP and unfolded proteins is mediated by a substrate-binding domain and a nucleotide-binding domain for ATPase activity, leading to protein folding and maturation. BiP also possesses a retrieval motif in its carboxyl terminal. When BiP is secreted from the ER, the Lys-Asp-Glu-Leu (KDEL) receptor in the post-ER compartments binds with the carboxyl terminal KDEL sequence of BiP and returns BiP to the ER via coat protein complex I (COPI) vesicular transport. Although yeast studies showed that BiP retrieval by the KDEL receptor is not essential in single cells, it is crucial for multicellular organisms, where some essential proteins require retrieval to facilitate folding and maturation. Experiments in knock-in mice expressing mutant BiP with the retrieval motif deleted revealed a unique role of BiP retrieval by the KDEL receptor in neuronal development and age-related neurodegeneration.